Her Dearest Sin - Wilson, Gaile (Ontario Harlequin, 2002)
Sebastian Sinclair mirrored his notable brothers in every way, even when it came to pursuing an intense, impossible love. Surely the flame in his heart could be nothing else, for it drove him to rescue a brave and beautiful Spanish noblewoman held prisoner to another mans dangerous desires!
Keywords: Love Story